Dialectics of Independence and Hegemony in the Novel Bakri Sang Guru Demonstran - Zulita, Diana; Syamsi, Kastam; Efendi, Anwar; Hartono, Hartono (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This research aims to describe the dynamics that occur as a result of conflict between two opposing parties, namely the minority party and the ruling party. The approach used is qualitative descriptive with a three-dimensional analysis of Norman model discourse Fairclough, namely texts, discourse practices, and sociocultural practices. The steps in this research include: reading the novel Bakri Sang Guru Demonstran; sorting data accordingly; and interpreting and concluding data. The results of this research are as follows following. First, text analysis shows that the author uses linguistic features to convey ideology about the ideal teacher figure and how the powerful try to intervene against minority groups. Second, seen from the perspective of discourse practice, text production is influenced by the author’s background as a practitioner of education and this novel was written to provide education to readers about the ideals of teachers and the challenges they face. Third, the sociocultural dimension shows that the flow story in the novel represents various problems that occur in society, especially in the field of education. That matter can be seen from various reports that appear in space public. Implications from the study This is possible to increase the breadth community (reader) understanding of the dynamics of the world of education and improvement system education through policy.